2012
DOI: 10.1073/pnas.1206587110
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 drives biphasic IL-13 production for noncanonical Type 2 immunity against hookworms

Abstract: Parasitic helminths are a major cause of chronic human disease, affecting more than 3 billion people worldwide. Host protection against most parasitic helminths relies upon Type 2 cytokine production, but the mechanisms that regulate interleukin (IL) 4 and 13 production from CD4 + T helper 2 cells (T H 2) and innate lymphoid type 2 cells (ILC2s) remain incompletely understood. The epithelial cell-derived cytokines IL-25 and IL-33 promote Type 2 responses, but the extent of functional redundancy between these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
176
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(184 citation statements)
references
References 52 publications
8
176
0
Order By: Relevance
“…[15][16][17]25,[34][35][36][37][38] Epithelium-derived IL-25 and IL-33, in particular, are important for driving IL-5 and IL-13 production from ILC2, the latter of which induces a number of responses, including goblet and tuft cell expansion, resulting in a strong positive feedback loop with increased production of IL-25 by epithelial cells. [15][16][17]31,[34][35][36][37] As a consequence, mice lacking IL-25 have less efficient expulsion of T. muris, 26 T. spiralis, 39 N. brasiliensis, 25,27,40 and H. polygyrus 28 worms. Furthermore, exogenous administration of IL-25 fails to restore expulsion in il13 À / À mice, 25,27 whereas the reverse is true, 15,17 illustrating that IL-25 acts upstream of IL-13 rather than directly on expulsion.…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17]25,[34][35][36][37][38] Epithelium-derived IL-25 and IL-33, in particular, are important for driving IL-5 and IL-13 production from ILC2, the latter of which induces a number of responses, including goblet and tuft cell expansion, resulting in a strong positive feedback loop with increased production of IL-25 by epithelial cells. [15][16][17]31,[34][35][36][37] As a consequence, mice lacking IL-25 have less efficient expulsion of T. muris, 26 T. spiralis, 39 N. brasiliensis, 25,27,40 and H. polygyrus 28 worms. Furthermore, exogenous administration of IL-25 fails to restore expulsion in il13 À / À mice, 25,27 whereas the reverse is true, 15,17 illustrating that IL-25 acts upstream of IL-13 rather than directly on expulsion.…”
Section: Transmissionmentioning
confidence: 99%
“…In contrast, once IL-33 is released in the setting of tissue damage, it can be further activated by granulocyte-derived proteases to exert its function. 48,49 Much like IL-25, it is important for driving IL-13 production by ILC2 during infection 31,35 and can also be recognized by other cell types. [50][51][52][53] Furthermore, whereas exogenous administration of IL-33 at early time points after T. muris infection promotes worm clearance, injection at later stages of infection does not induce expulsion, 29 suggesting that there is an early window of opportunity in which it exerts its effects.…”
Section: Transmissionmentioning
confidence: 99%
“…These original studies showed that IL-25-and IL-33-responsive ILC2s were critical for the development of type 2 cytokine -associated inflammation and goblet cell hyperplasia that facilitate expulsion of N. brasiliensis in the absence of adaptive immunity (Moro et al 2010;Neill et al 2010;Price et al 2010). A more recent study has shown that IL-33 is critical for the induction of IL-13 production by ILC2s to mediate worm expulsion (Hung et al 2013). In addition to their role in mediating protective immunity to helminth parasites, ILC2s also contribute to the development of pathologic type 2 inflammation, as they promoted gut inflammation in an IL-25-dependent fashion in a murine model of oxazalone-induced colitis ).…”
Section: Ilc2s In the Gutmentioning
confidence: 99%
“…Multiple reports indicate that IL-33 is a potent activator of IL-13-producing ILC2s in allergic airway inflammation (Bartemes et al 2012;Beamer et al 2012;Mjosberg et al 2012;Salmond et al 2012;Hung et al 2013;Shaw et al 2013), but other epithelial cell-derived cytokines, bioactive lipids, and inflammatory factors also contribute to the development of pathogenic ILC2 responses in the lung. A recent study has shown that TSLP can contribute to ILC2 activation that promotes corticosteroid resistance in the context of IL-33-mediated airway inflammation (Kabata et al 2013).…”
Section: Ilc2s and Allergic Airway Inflammationmentioning
confidence: 99%
“…Studies in IL-33-deficient mice indicate that IL-33 plays important roles in type-2 innate immunity and innate-type allergic airway inflammation (9)(10)(11)(12)(13). Indeed, IL-33 is a key activator of the recently described group-2 innate lymphoid cells (ILC2s, natural helper cells, nuocytes) (14)(15)(16)(17).…”
mentioning
confidence: 99%